Chimeric retinoic acid/thyroid hormone receptors implicate RAR-alpha 1 as mediating growth inhibition by retinoic acid. - Schilthuis, J G (1993)
Retinoic acid (RA) affects the growth and differentiation of cells in culture, usually to decrease the growth rate. In amphibian limb regeneration RA has the remarkable ability to affect pattern formation by changing positional identity, but its initial action on the limb is to inhibit division of the blastemal progenitor cells. Newt limb blastemal cells also show this inhibition in culture. In order to investigate the role of different RA receptors (RARs) in the RA response, the hormone binding domain of the newt RARs alpha 1 and delta 1 was replaced with the corresponding region from the Xenopus thyroid hormone receptor-alpha (TR-alpha). In COS cells transfected with each of the chimeras, transcription was activated after exposure to thyroid hormone (T3). Their profile of activity on three different response elements was indicative of RAR specificity and not TR specificity. After transfection of cultured newt blastemal cells with a DNA particle gun, the chimeras were equally active in stimulating T3-dependent transcription of two different synthetic reporter genes. Blastemal cells were transfected with chimeras or control plasmids along with a marker plasmid expressing beta-galactosidase, exposed to RA or T3 and labelled with [3H]thymidine followed by autoradiography. The alpha 1 chimera gave T3-dependent inhibition of growth, comparable to the effect exerted by RA itself, whereas the delta 1 chimera and control plasmids were inactive. The results imply that RAR-alpha 1 mediates the effects of RA on blastemal cell growth.